Analisis Rasionalitas Penggunaan Antibiotik Profilaksis Pada Pasien Bedah Sesar - Husnawati - Husnawati (LPPM Universitas Abdurrab, 2022)
Prophylactic antibiotics are antibiotics given before, during and up to 24 hours postoperatively in cases where clinically there are no signs of infection, but prophylactic antibiotics are given to prevent surgical site infections, including cesarean section. The purpose of this study was to examine the rationale for the use of prophylactic antibiotics in cesarean section at a PMC hospital Pekanbaru. This type of research is a qualitative study, using descriptive methods and data obtained from medical records retrospectively, using purposive sampling technique on 69 medical records that meet the inclusion criteria. The results showed that the use of prophylactic antibiotics at cesarean section was 66.67% rational and 33.33% irrational. The measured rationality is the right indication (100%), right drug (100%), right patient (100%), right regimen (right dose (95.61%), right frequency (79.82%), right time of administration (100%), the right way of administration (100%) given intravenously), and alert for side effects (100%)